A moderated-mediation model of career adaptability and life satisfaction among working adults in Malaysia - Siew, Imm Ng; Qin, Hui Lim; Jun, Hwa Cheah; Jo, Ann Ho; Keng, Kok Tee (Springer Nature, 2022)
Career adaptability refers to the concept of individuals taking charge of their own career development by staying concern, control, curious and confident. Since the career adaptability measurement scale was made available in 2012, the concept has been extended to various samples and consistently found its applicability across many countries. This study intends to continue with this line of research by extending its nomological network to another country (i.e. Malaysia) using a unique sample (work and study adults who enroll in a post-graduate degree program). We also responded to the call for identifying the conditions and mechanisms in which career adaptability may bring differential effect to the life satisfaction outcome. Based on 200 sets of data collected, it was found that career adaptability predicted life satisfaction through a moderated (connectedness) and mediation (job satisfaction) relationship. The results provided empirical evidence on the universality of the career adaptability scale, Career Construction Theory and the Life-Span, Life-Space theory. Juggling between work and studies, individuals with higher career adaptability was found to enjoy higher job satisfaction under the condition of high connectedness (getting support and help from family, university, neighbour and friends). The joy of job satisfaction then spilt over to other life domains and manifested in life satisfaction.